Temperature Control System For Fertigation Application - Ismail, Mohd. Farid; Abdullah, Muhammad Ilman Hakimi Chua; Abu Bakar, Muhammad Fairuz; Ahmad, Azrin; Mokhtar, Mohd Sulhan; Hamzah, Luqman Hakim; Othman, Muhammad Nur; Siam, Effendy Onn (UTeM, 2018)
The aim of this project proposal is to solve an industrial problem raised by GM Peladang Sdn Bhd by providing an automated temperature controlled system equipped with automated water stirrer system for fertigation tank. GM Peladang produced vegetables and fruits using fertigation and Nutrien Film techniques. This company wish to increase their production by providing lower temperature fertilizer water to their plants. The chosen method used to solve this problem is to deliver fertilizer solution at temperature range between 20°C and 25°C is by chilled water system. The whole system will be automated inclusive with displayable measured parameters on the control panel to achieve the optimum fertilizer solution temperature for irrigation process. The lead time taken to finish this project is within six (6) months with total cost required as low as RM 27,300.